Prenatal Diagnosis of Dystrophinopathy and Cytogenetic Analysis in 303 Chinese Families - Mengmeng Li (Wolters Kluwer Health, 2021)
Abstract. Objective:. This study was to supply information of the Duchenne muscular dystrophy (DMD) mutational spectrum in 303 Chinese families and further offer 5-year clinical experience of DMD/Becker muscular dystrophy genetic counseling and prenatal diagnosis. Methods:. In this retrospective cohort study, three hundred and five pregnancies in 303 pregnant women who has a birth history of DMD/Becker muscular dystrophy patients underwent prenatal diagnosis using multiplex ligation-dependent probe amplification followed by Sanger sequencing between January 2014 and December 2018 at Peking Union Medical College Hospital. The mean age of pregnant women was (33.0 ± 4.1) years old. Karyotype analysis was performed to exclude fetal abnormal karyotype. Results:. The detection rate of DMD gene mutation in 303 probands was (296/303) 97.7% with seven families having a negative genetic diagnosis. The mutational spectrum comprised of large arrangements in 288/303 (95.0%) and small mutations in 8/303 (2.6%). Carrier testing was performed among 204 pregnant women among whom, 108 mothers had the same mutation as family proband. Of the 305 pregnancies underwent prenatal diagnosis, 55 of 173 male fetuses were affected. We also performed karyotype analysis and found three abnormal karyotypes of trisomy 21. We even found a fetus with DMD gene mutation and trisomy 21 in a same fetus by further analysis. We also identified two times of germline mosaicism. Conclusion:. This study demonstrated the distribution and mutation profile of 303 probands and 305 fetuses. Furthermore, considering the possbility of maternl germilne mosaicism, prenatal diagnosis should be suggested to mothers with a proband whether they carry the causative mutation in their blood or not.